Analysis of the Implementation of the Generative Learning Model on the Achievement of Class X SMA Budisatrya Medan - A Zebar; Sari Ramadhani; Dara Aisyah (Outline Publisher, 2024)
The problem in this research is the low student learning outcomes. The aim of this research is to determine the influence of the Generative Learning Model on the Economics Learning Outcomes of Class This research was conducted in class X of Medan Budisatrya Private High School FY 2014/2015. The population in this study was all class X of Medan Budisatrya Private High School which consisted of 4 classes. This research sample consisted of X-3 as the experimental class and X-4 as the control class. The sampling technique used was simple random sampling. The instrument or data collection technique in this research is a test of student communication learning outcomes in the form of multiple choices of 20 items. Meanwhile, the data analysis technique used is the normality test, homogeneity test and to test the hypothesis the t test is used. The results of data analysis show that the average value of the experimental class is 64.75 with a standard deviation of 13.96, while the average value of the control class is 60.75 with a standard deviation of 13.99. Hypothesis testing is carried out using the t test statistical. From the results of the hypothesis calculation, the t_count is 5,750 and the t_table is 1,994. In other words, the hypothesis is accepted. From these results it can be concluded that there is an influence of the use of the Generative Learning Model on the Economic Learning Outcomes of Class